Better Luck Next Time: Learning through Retaking - Verónica Frisancho Robles; Kala Krishna; Sergey Lychagin; Cemile Yavas (Inter-American Development Bank (IDB), 2014)
This paper provides some evidence that repeat taking of competitive examsmay reduce the impact of background disadvantages on educational outcomes. Using administrative data on the university entrance exam in Turkey, the paper estimates cumulative learning between the first and the nth attempt while controlling for selection into retaking in terms of observed and unobserved characteristics. Large learning gains measured in terms of improvements in the exam scores are found, especially among less advantaged students.
hdl:11319/4785
Keywords: C13; C38; I23; I24; 330; Learning; Higher education; Factor models; Selection